Anti-graft war: social media as tools for creating awareness for Biometric Verification Number (BVN) registration in Nigeria (Journal of Management and Social Sciences, 2021)
Social media networks have been found to be potent channels of communication to the masses. Facebook and Twitter in particular have been found to be highly influential in sensitizing and mobilizing the populace towards vital issues such as elections, public health, protests like #OccupyNigeria and #EndSARS. Against this background, the paper interrogated the effectiveness of social media’s usage in creating awareness for the Biometric Verification Number (BVN) registration of bank customers aimed at checking illicit financial transactions in Nigeria. The theoretical underpinning of the paper was anchored on diffusion of innovation, and uses and gratifications theories. Whereas the study employed survey method, its population comprised bank customers resident in Abeokuta, the capital city of Ogun State. A sample of 150 respondents was selected randomly and a structured questionnaire was administered to gather quantitative data. Findings showed that social media networks were effective in informing and mobilizing bank customers about BVN registration. Majority of the respondents became aware and knew about BVN project through the social media accounts of banks, email and bulk SMS. Also, the extent to which banks utilized the various social media networks was very high. But the study concluded that respondents lacked confidence in email and SMS about BVN for fear of rising incidence of cyber fraud. Therefore, it recommended that the Bankers’ Committee of the Central Bank of Nigeria (CBN) should direct banks to consolidate using mainstream and social media.KeywordsSocial media, BVN registration, awareness, cyber fraud, anti-graft war